2008
DOI: 10.1055/s-2008-1074583
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of the Mexican Anxiolytic and Sedative PlantGalphimia glaucaUsing Nuclear Magnetic Resonance Spectroscopy and Multivariate Data Analysis

Abstract: Galphimia glauca is popularly employed in Mexico for the treatment of central nervous system disorders. Pharmacological and phytochemical studies have resulted in the identification of the anxiolytic and sedative principle consisting of a mixture of nor-secofriedelanes, named the galphimine series (1 - 9). These active constituents were found in plants collected in the vicinity of a restricted region in Central Mexico, where this species is abundant. A metabolic profiling carried out by means of 1H-NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 12 publications
1
60
0
1
Order By: Relevance
“…Our two previous metabolic profiling studies of Galphimiaglauca using 1 H-NMR spectroscopy and multivariate data analysis, clearly showed differences in metabolic profiles of Galphimiaglauca populations in levels of sedative, anxiolytic and anti-inflammatory activities that were clearly related to the region of collection (Cardoso-Taketa et al, 2008; Sharma et al, 2012). Two of the populations (GM and QJ) were particularly high in galphimines (active populations), whereas all of the other populations (MM, MT, MC, JG and CT) did not seem to have detectable levels of these secondary metabolites.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our two previous metabolic profiling studies of Galphimiaglauca using 1 H-NMR spectroscopy and multivariate data analysis, clearly showed differences in metabolic profiles of Galphimiaglauca populations in levels of sedative, anxiolytic and anti-inflammatory activities that were clearly related to the region of collection (Cardoso-Taketa et al, 2008; Sharma et al, 2012). Two of the populations (GM and QJ) were particularly high in galphimines (active populations), whereas all of the other populations (MM, MT, MC, JG and CT) did not seem to have detectable levels of these secondary metabolites.…”
Section: Introductionmentioning
confidence: 73%
“…The presence of galphimines in the GM and QJ populations and the absence in the MM, MT, MC, JG and CT samples, has also been confirmed via high-performance liquid chromatography (HPLC) analysis. Partial least square regression discriminant analysis (PLS-DA) confirmed a positive correlation between the presence of galphimines and the sedative and anxiolytic responses displayed by those extracts (Cardoso-Taketa et al, 2008; Sharma et al, 2012). The differences seemed to indicate that the chemical profiles exhibited among the Galphimiaglauca populations collected in the different regions of Mexico, could be related to geographical, climatic, or soil conditions.…”
Section: Introductionmentioning
confidence: 85%
“…For example, Galphimia glauca, a Mexican herb, has been used for treating central nervous disorders. Mouse bioassay experiment revealed that G. glauca samples collected from six locations possess different anxiolytic and sedative activity (61).…”
Section: Metabolomics-based Identification Of Bioactive Phytochemicalsmentioning
confidence: 99%
“…But for all methods, one should also consider the time needed for extraction and sample preparation, which in the case of GC is far more complicated, as a chemical derivatization step is required, whereas in the case of NMR the extraction can be done with the deuterated NMR solvent. [24][25][26][27][28][29][30][31][32][33] …”
Section: High-throughput Analysismentioning
confidence: 99%
“…These tools can be applied in a broad variety of applications: quality control of medicinal plants (Ephedra spp., [24] Ginkgo biloba [25] ), plant resistance against pests and diseases (Senecio spp., [26] Brassica rapa, [27] Catharanthus roseus, [28] tobacco [29] ), identifi cation of active compounds in medicinal plants (Galphimia glauca [30] ), and chemotaxonomy (Ilex spp., [31] cannabis, [32] Strychnos spp. [33] ).…”
Section: Public Metabolomic Databasementioning
confidence: 99%